AKIBAT HUKUM PROSES PEMBUKTIAN TERHADAP TERDAKWA YANG TIDAK DIDAMPINGI PENASIHAT HUKUM DALAM PERSPEKTIF HUKUM ACARA PIDANA (STUDI PUTUSAN PENGADILAN NEGERI TEMBILAHAN NOMOR 215/Pid.Sus/2019/PN Tbh.) - Alex Oktavian; Hery Firmansyah (Jurnal Hukum Adigama, 2022)
The Criminal Procedure Code adheres to the principles contained in the provisions stipulated in Articles 50 to 64 ofthe Criminal Procedure Code which can be concluded as the rights of the suspect or defendant. Among the rights ofa suspect or defendant is the right to obtain legal assistance from legal counsel which can be provided at every levelof examination and in the context of rapid distribution of justice for everyone which is carried out quickly, cheaplyand simply. In the practice of implementing litigation, the provision of legal assistance to the community is often notcarried out. One of them is in the case that the author will discuss, the Decision of the Class II A TembilahanDistrict Court number 215/Pid.Sus/2019/PN Tbh which sentenced Kamarek bin Ruslan to 6 years in prison and afine of Rp. 3 billion, subsidiary to 6 months in prison. In the a quo trial, the Defendant who is an illiterate person isnot accompanied by a Legal Counsel so that he cannot fight for his rights as a Defendant. In this paper, the authorwill examine the legal consequences that arise in the court process where the defendant is not accompanied by alegal advisor, as well as legal protection for the rights of the defendant who is not accompanied by a legal advisorduring the trial.